ANALYSIS OF POTENTIAL ECONOMIC SECTOR ON GOWA DISTRICT, INDONESIA - Ramli, Anwar (Archives of Business Research, 2014)
Anwar Ramli 2014 ( Analysis Of Potential Economic Sector On Gowa District, Indonesia ) The study aims at discovering the superior sector in Gowa district and examining the economic growth in Gowa district. The study is a quantitative research with figures-based regional micro economic that verificative-quantitative in nature, which use the formula on regional economic on date of regional macro in Gowa district. Data were collected by determining the types of data adjusted with quantitative data. The measurement period used time series data with five-year period, from 2008 to 2012. Data were analyzed by employing economic analysis method, namely Location Quotient (LQ) analysis and Shift Share analysis. The results of the study reveal that the result of LQ analysis determined that the basis sectors in Gowa district were agriculture, finance, and services; the non-basis sectors were mining and quarrying sector, processing industry, electricity gas and water supply, building construction, trade, hotel and restaurant, as well as transportation and communication. The results of Shift Share analysis indicated that the sector which have rapid growth in the province level (PS+) were electricity gas and water supply, building construction, trade, transportation and communication as well as finance leasing sector. The economic sectors which have competitive superior or competitiveness (DS+) were mining, transportation and communication, as well as finance and leasing sectors. Keywords: Potential Economic Sector, Growth,Location Quotient.